2006
DOI: 10.1002/art.21729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of classical complement pathway activation in rheumatoid arthritis: Measurement of C1q–C4 complexes as novel activation products

Abstract: Objective. Novel activation products that are stable and minimally susceptible to in vitro artefacts have recently been described in the classical complement pathway. The present study assessed circulating levels of these products, i.e., covalent complexes between the recognition molecule of the classical pathway (C1q) and activated C4, in plasma samples from patients with rheumatoid arthritis (RA) to establish the relationship between these levels and the clinical and immunologic parameters in these patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…The complement system has been shown to play a role in both initiating the inflammatory state as well as in maintaining the inflammation during chronic disease. Complement activation products, such as C3d (34), C1q-C4 complexes (35), sC5b-9, and the fragment Bb (36), can be found in the synovial fluid of patients with active arthritis, indicating ongoing activation of complement. Mice deficient in C3, factor B, and C5 are resistant to collagen-induced arthritis, an experimental model of rheumatoid arthritis, showing the importance of complement in the effector phase of chronic arthritis (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…The complement system has been shown to play a role in both initiating the inflammatory state as well as in maintaining the inflammation during chronic disease. Complement activation products, such as C3d (34), C1q-C4 complexes (35), sC5b-9, and the fragment Bb (36), can be found in the synovial fluid of patients with active arthritis, indicating ongoing activation of complement. Mice deficient in C3, factor B, and C5 are resistant to collagen-induced arthritis, an experimental model of rheumatoid arthritis, showing the importance of complement in the effector phase of chronic arthritis (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…C1q is known to play an important role in immune complex diseases, such as systemic lupus erythematosus, Arthus reaction, autoantibody-induced arthritis, glomerulonephritis, and experimental autoimmune encephalitis. 11,[64][65][66] In addition, mast cells have been associated with these diseases. 36,[67][68][69][70] Our findings provide a molecular mechanism linking C1q and activation of these inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Complement factors and receptors have been called to play an important role in RA since the first report from Brodeur in 1991 (14), and it is evident that synthesis and activation of complement take place at distinct sites within rheumatoid synovium (15). Reduced levels of native complement components and increased levels of complement metabolites in the synovial fluid and synovial tissue of RA patients have implicated complement in the pathogenesis of RA (16). It has been suggested that key components in complement activation, such as C3 and B, are produced locally in RA synovium rather than being plasma derived (17).…”
Section: Complement and Autoantibodiesmentioning
confidence: 99%